Mathematical Modeling of the Pylon-Type Metro Station Design Based on Numerical Analysis - Fedorov , K. Ye.; Tiutkin, O. L. (Science and Transport Progress, 2025)
Purpose. The authors set the goal of conducting mathematical modeling of the pylon-type metro station structure based on numerical analysis using the finite element method, as well as searching for components of the stress-strain state and determining the strength of the combined reinforcement, which is constructed based on the New Austrian tunneling method. Methodology. To achieve the task, a finite element model of a pylon-type metro station was developed in the professional calculation complex Structure CAD for Windows. The model fully reflects the properties of the combined (temporary and permanent) lining of a pylon-type metro station. Half of the pylon-type metro station was modeled; the model was given deformation characteristics taken from real engineering and geological studies. Also, a set of boundary conditions was applied to the model, which corresponds to the real deformation of the system, as well as the combination of loads. Findings. During the numerical analysis, representative information was obtained on the stress-strain state of the pylon-type metro station and it was found that the presence of passages, as well as sections of the passage transition into the pylon and vice versa, indicates their significant redistribution. A detailed analysis of the frame displacements proved that the deformation of the frame of the middle and side tunnels confirms the almost uniform movement of the station structure. The maximum values of stresses in the permanent frame of the pylon-type metro station were determined. The presence of a system of pylons, as well as passages, forms a non-uniform stress state, which, in combination with a uniform deformed state, represents a defining advantage of the station structure of this type. Originality of the results lies in the first obtained during mathematical modeling of the stress-strain state of the structure of a pylon-type station, which is being built in strong soils based on NATM. Practical value. It is characterized by the results of the analysis of the strength of the combined (temporary and permanent) lining of a deep-buried pylon-type station.